The mechanism underlying hypaconitine-mediated alleviation of pancreatitis–associated lung injury through up-regulating aquaporin-1/TNF-α - Gao, Jiali; Bao, Lidao; Zhang, Aiwu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Acute pancreatitis–associated lung injury (APALI) is one of the most common and most dangerous form of extra-pancreatic organ damage in severe acute pancreatitis (SAP). The treatment options for SAP were limited thus far; as a result, approximately 60%–80% of patients with SAP would die within a week. Hypaconitine (HC), one of the most important active ingredients in a Mongolian traditional medicine Radix Aconiti Kusnezoffii has an excellent anti-inflammatory effect. Materials and Methods: To ascertain whether HC has a protective effect against APALI, we investigated the therapeutic effects and the underlying mechanisms in vivo and in vitro and attempted to elucidate the mechanism in detail. In this study, APALI rats and human pulmonary microvascular endothelial cells were treated with therapeutic doses of HC after establishing a model with sodium taurocholate and lipopolysaccharide, respectively. Results: Serum amylase and lipase activity, lung wet/dry weight ratio, lung myeloperoxidase activity, and pancreatic and lung histopathological changes showed that HC alleviated APALI in a dose-dependent way, which can be abolished by an aquaporin-1 (AQP-1) knockdown. The results of the reverse transcriptase polymerase chain reaction, Western blot, and immunohistochemical staining confirmed the expression of AQP-1, a kind of transmembrane protein that mainly distributed in the membranes of pulmonary cells and contributed to maintain water balance in the body by interacting with tumor necrosis factor-alpha (TNF-α), is negatively associated with APALI. On the contrary, HC treatment up-regulated AQP-1 expression and down-regulated the TNF-α expression as a consequence in APALI. Conclusion: These results suggest that HC has a good anti-inflammatory therapeutic effect on APALI with a possible underlying mechanism that affects the AQP-1/TNF-α pathway.